The Ambiguity of Living Qur'an Studies in Indonesia - Syam, Masiyan M; Nurfadliyati, Nurfadliyati (Institut Agama Islam Negeri (IAIN) Curup, 2024)
New clusters of Living Qur'an studies are finding a saturation point. This is because on campus the models of Living Qur'an studies revolve around the same themes, around khataman, sometimes only the place changes. On the other hand, the definition of the Living Qur'an itself is still not established. So that in the practice of Living Qur'an studies there is a lot of confusion, some mention living Qur'an as a method, research approach, and even mention it as a concept of science. This article explains what is ambiguity in the study of living Qur'an. This research is a literature study with interviews and documentation to obtain data. The result found is that Living Qur'an is a phenomenon so that it is open to study both with sociology and anthropology. And it is important for living Qur'an scholars to pay attention to the study of ulumul Qur'an because that is what distinguishes it from the study of anthropology or pure sociology.